Extração de Pectina de casca de melancia : produção de biofilmes e aplicação de Pectina cítrica como cobertura comestível na conservação pós-colheita de tomate cereja - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
Although watermelon is appreciated and consequently has a high production in Brazil, this fruit generates excessive amounts of waste, such as the rind, and is discarded inappropriately in the environment. However, from the watermelon rind, pectin is obtained, which can be used in various applications, such as the manufacture of edible film packaging, and can be used to extend the shelf life of fruits, such as cherry tomatoes, which are a vegetable among the most produced and has characteristics that please the consumer. Knowing this, the objective of this work was to produce films based on pectin extracted from the rind of watermelon, and to evaluate the effect of this edible coating on the postharvest conservation of cherry tomatoes. In the first experiment, initially, the watermelon rind was dried in an oven at 65±3ºC and then pectin extraction was performed using a microwave at 450 W, for 12 minutes, and the sample solution at pH 1,52. As for the film, pectin was diluted in distilled water at 60±1°C, and the solution was homogenized by stirring, and during this process glycerol was added. Then, the solution was placed in a polypropylene plate and sent to an oven at 60±3°C until constant weight. The experimental design was completely randomized in a double factorial scheme 4x4, with four replications, with different concentrations of watermelon pectin (1.5%; 2.0% and 2.5%) and 2.0% of commercial pectin (control), and different concentrations of glycerol (0%; 0.5%; 1.0% and 1.5%). The variables analyzed were: yield, thickness, coloration, solubility, permeability, degree of esterification and mechanical property. For the second experiment, the edible covering was used, which showed the best results in the first experiment, using a completely randomized design in a 5x10 double factorial scheme, with different immersion times (0, 1, 2, 3, 4 and 5 minutes) and days of analysis (0, 4, 8, 12, and 16 days), with four repetitions and six fruits each. After application of the edible coatings, the fruits were placed on expanded polystyrene containers and stored in B.O.D. at 10°C. The analyzed variables were: mass loss, color, firmness, soluble solids, titratable acidity, maturation index, vitamin C, total extractable polyphenols and total antioxidant activity. The data from the experiments were submitted to analysis of variance, at 5% probability, and, when significant, regression analysis for the first experiment and principal component analysis and hierarchical grouping for the second experiment. The software used for statistical analysis were Sisvar 5.6 and Rstudio. Based on the results obtained, the best concentration for film formulation was 2.0% commercial pectin and 1.5% glycerol. Regarding the preservation of the fruits, immersion in the covering for 4 minutes was more effective, with the fruits being kept in an ideal condition for consumption until the 12th day of analysis.
Keywords: Citrullus lanatus; Solanum lycopersicum; Caracterização do tomate cereja; Armazenamento; Pectina; Citrullus lanatus; Solanum lycopersicum; Characterization; Quality; Storage; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA